Carboxypeptidase inhibitors from Solanaceae as a new subclass of pathogenesis related peptide aiming biotechnological targets for plant defense - Gomes, Geniana da Silva; Espósito, Paula Corrêa; Baracat-Pereira, Maria Cristina (Frontiers in Molecular Biosciences, 2023)
Plant protease inhibitors play a crucial role in inhibiting proteases produced by phytopathogens and exhibiting inhibitory effects on nematodes, fungi, and insects, making them promising candidates for crop protection. Specifically, carboxypeptidase inhibitors, a subset of proteinase inhibitors, have been extensively studied in potato and tomato of Solanaceae plant family. However, further research is needed to fully understand the functions and biotechnological potential of those inhibitors in plants. This work aimed to in silico characterize carboxypeptidase inhibitors from Solanaceae as potential antimicrobial and defense agents focused on biotechnological targets. The methodology employed involved search in UniProt, PDB, KNOTTIN, NCBI, and MEROPS databases for solanaceous carboxypeptidase inhibitors, phylogenetic relationships and conservation patterns analyzes using MEGA-X software and Clustal Omega/MView tools, physicochemical properties and antimicrobial potential prediction using ProtParam, ToxinPred, iAMPred, and APD3 tools, and structural features prediction using PSIPRED. A systematic literature search was conducted to identify relevant studies on Solanaceae carboxypeptidase inhibitors and their activities against pathogens. The selected studies were reviewed and the main findings compiled. The characterization of Solanaceae carboxypeptidase inhibitors proposed for the first time the global sequence consensus motif CXXXCXXXXDCXXXXXXCXXC, shedding light on carboxypeptidase inhibitors distribution, sequence variability, and conservation patterns. Phylogenetic analysis showed evolutionary relationships within the Solanaceae family, particularly in Capsicum, Nicotiana, and Solanum genera. Physicochemical characteristics of those peptides indicated their similarity to antimicrobial peptides. Predicted secondary structures exhibited variations, suggesting a broad spectrum of action, and studies had been demonstrated their activities against various pathogens. Carboxypeptidase inhibitors are being proposed here as a new subclass of PR-6 pathogenesis-related proteins, which will aid in a focused understanding of their functional roles in plant defense mechanisms. These findings confirm the Solanaceae carboxypeptidase inhibitors potential as defense agents and highlight opportunities for their biotechnological applications in pathogen control.